(3cJGH eSfO CHh HcQ hYeQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3Chdg fGbU hChd GdehLhO efg (B:" (3hcGf Ydi Hf CHiWGdH fLYdg JHdZ SJI gh SGOSge , aEPG RGOhG Ydi Pdc CYWGg GdSOS s
(3BNQgG (B:s
(3Yf SYjO Hf GdeSjH bGd (B: (3CJi QLd YeQ Hf GdNWGH dg KdGK fShI abGd (B:(3Efge Ydjg cXgQ Ceg abGd YeQ (B: (3Ydjg caGQI hGMO YH YOb BNQ GdLRA GdNGeS s
(3cJHJ GdQehR ajgG HGdMeQIs
(3YdjgG JUMjMGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI GdMSjfi s
Keywords: (3GdMOjK h GdeUWdMs